Transformasi IAIN Menjadi UIN Sebuah Dilema Pendidikan Tinggi Islam - Amir Syaifurrohman (LPPM UIN Saizu Purwokerto, 2021)
Education is the most important factor in the progress of human civilization. Education forMuslims is a must to be prioritized. A good Islamic education system will lead to the realizationof the ideals of a civilized Islamic society. In the current development, the reality isthat Islamic educational institutions still have many problems to solve. IAIN which has beenthe pinnacle of Islamic higher education institutions is still not able to produce educationaloutputs that can answer the problems of human life. Religious studies at IAIN have backfiredin the world of Islamic education. The change of IAIN to UIN is expected to be a new lightin the world of Islamic education. Islamic educational institutions that previously only gavebirth to Islamic thinkers will later give birth to professionalism in the fields of science andtechnology. To realize this hope is certainly not as easy as turning the palm of the hand, ittakes a long struggle to organize all the aspects needed to support the success of an Islamiceducation. So that the hope will give birth to a new civilization in the Islamic world. However,there is some concern that UIN graduates will only produce outputs that are only good atscience but are empty of Islamic values.